Western Northern Luzon Isotopic Evidence of Transition from Proto-South China Sea to South China Sea Fossil Ridge Subduction - Liu, Hai-Quan (Archīum Ateneo, 2019)
Temporal geochemical comparisons are conducted for representative magmatism from western Northern Luzon to reconstruct the Cenozoic tectonics. Oligo‐Pleistocene magmas from western Northern Luzon display elemental and Sr‐Nd‐Hf‐Pb‐O isotope geochemistry similar to intraoceanic arc magmatism, consistent with derivation from the mantle wedge, coupled with fractional crystallization. Specifically, the Oligo‐Miocene (~26.8–15.6 Ma) Central Cordillera diorite complex samples exhibit a negative correlation between Sr‐Nd isotopes, consistent with mantle metasomatism by fluids/melts released from pelagic sediments. The Mio‐Pleistocene samples (~9 Ma) magmatism exhibit intraoceanic arc isotopic signatures, suggestive of a chemical imprint from subducted pelagic sediments. The Mio‐Pleistocene (